The Politics of Sacrifice: Liberation, Deformity, and Odin in The Book of Ahania - Choe, Sharon (Scandinavian-Canadian Studies / Études scandinaves au Canada)

(untitled) (Association for the Advancement of Scandinavian Studies in Canada, 2026)
In William Blake’s The Book of Ahania (1795), the figure Fuzon is killed by his tyrant father Urizen before being sacrificed in a pseudo-Crucifixion scene. While the Christian iconography is apparent, a closer textual reading of his subsequent deformity reveals that this scene also has roots in the British eighteenth-century Northern antiquarianism, a literary and artistic movement interested in the ancient North. In his poetry, Blake’s engagement with Northern antiquarianism is visible in disabled and deformed figures that embody both liberation from and repression of State, religion, and nation. In The Book of Ahania, Blake examines the tension between Norse primitive warmongering and Gothic liberty as the foundations of a body politic—that of Urizen’s oppressive State Religion—where Fuzon’s death and deformity extends beyond Christological analogues to become a type of Odinic sacrifice. In this poem, I suggest that Fuzon transforms into a composite image of Odin-as-chieftain who seeks liberation from Rome, and Odin-as-priest.